1961
DOI: 10.1111/j.2153-3490.1961.tb00100.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Meanders on the Kinetic Energy Balance of the Gulf Stream

Abstract: Calculations have been made, using surface velocity observations, of the horizontal transfer of kinetic energy from meanders to mean flow at two separate localities in the Gulf Stream System. In both cases, it was found that there was a surface flow of kinetic energy from the meanders to the mean flow, exactly opposite to what would be expected if the meanders were frictionally driven. The observations suggest that the meanders derive cnergy from sources other than the kinetic energy of the mean flow. The role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

1962
1962
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 9 publications
(1 reference statement)
3
27
0
Order By: Relevance
“…South of 33°S, cross‐stream differences in the BTC are evident. Eddy‐to‐mean energy conversion occurs along the cyclonic sides (inshore), whereas eddies are fed by the energy of the time‐mean flow on the anticyclonic sides (offshore), as highlighted in the studies of Webster [], Brooks and Niller [1977], Hood and Bane [], Rossby [], and Dewar and Bane []. The analysis of the mass and momentum fields shows that baroclinic and barotropic instabilities occur simultaneously, i.e., the current features a mixed instability process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…South of 33°S, cross‐stream differences in the BTC are evident. Eddy‐to‐mean energy conversion occurs along the cyclonic sides (inshore), whereas eddies are fed by the energy of the time‐mean flow on the anticyclonic sides (offshore), as highlighted in the studies of Webster [], Brooks and Niller [1977], Hood and Bane [], Rossby [], and Dewar and Bane []. The analysis of the mass and momentum fields shows that baroclinic and barotropic instabilities occur simultaneously, i.e., the current features a mixed instability process.…”
Section: Resultsmentioning
confidence: 99%
“…Energetic analyses have been used in several other regions of the global ocean since the 1960s. Most studies have been conducted in WBCs, especially in the Gulf Stream [Webster, 1961[Webster, , 1965Oort, 1964;Rossby, 1987;Dewar and Bane 1985, 1989a, 1998bCronin and Watts, 1996;Greatbach et al, 2010;Kang and Curchitser, 2015], Kuroshio Current [Nishida and White, 1981;Hall, 1991;Bishop et al, 2013], East Australian Current [Mata et al, 2006], and Antarctic Circumpolar Current [Bryden, 1979;Phillips and Rintoul, 2000;Walkden et al, 2008]. In the North Atlantic Ocean, some studies have observed the influence of bathymetry on the destabilization of the Gulf Stream as it flows over the bathymetric feature known as the Charleston Bump and moves away from the coast in the Cape Hatteras area.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that baroclinic conversions of either sign dominate over barotropic conversions in deep water. One may compute the maximum deep-water transfers possible by either process, assuming that eddy potential energy is about equal to eddy kinetic energy (an observed fact) and that [Webster, 1961' Oort, 1964 and below the thermocline . This is a region characterized by meander amplitudes that decay in the direction of propagation [Hood and Bane, 1983].…”
Section: Version Rates Are U'v'c•t•/c•y and V't'c•/c•y Respectivelymentioning
confidence: 74%
“…In this section we examine the classical barotropic and baroclinic energy exchange rates between the mean field and linear large-scale waves [Brooks and Niiler, 1977;Webster, 1961] to test whether these instabilities operate in the deep layers of the Gulf Stream. The barotropic and baroclinic con- [Bryden, 1979] Table 3).…”
Section: Energeticsmentioning
confidence: 88%
See 1 more Smart Citation